THE INDIVIDUAL ACADEMIC WORK IN THE VOCATIONAL TRAINING OF PHYSICAL EDUCATION AND SPORT SPECIALISTS - Gheorghe VOLCU; Irina VOLCU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2023)
In this article we approach the topic of individual academic work in the vocational training of specialists of physical education and sport. This activity, very important in the university educational process, is promoted both within classroom hours and outside of them, but most often individual work is promoted within seminars, laboratory hours, projects, practical works, competitions and performing tasks at home. Individual work is one of the main forms of study of subjects by students specializing in physical education and sport, expressed by studying theoretical topics, performing control and laboratory work and applying knowledge to carry out semestrial, periodical and final assessments. Starting from the analysis of references on the mentioned topic and ending with qualitative and quantitative reflections from the specific university context, we highlight the aspect of the individual work of the students from the point of view of professional training. It is carried out for the purpose of students specializing in physical education and sport acquiring general and special professional skills, including the ability to use the knowledge acquired in the professional field. An important result of the individual work of students is the formation of their ability to train individually in order to obtain knowledge, skills, competences for the purpose of continuous professional development.